Social Networks Among Small-Scale Fishermen in Cilincing As a Strategy to Dealing With Uncertainty in Finding Fish Resources (Komunitas, 2018)
This study discussed about utilization of social networks owned by Cilincing’s small scale fishermen as strategy to facing uncertainty in the search of fish resources. The uncertainty conditions occurs due to environmental changes caused by the reclamation project of the bay of Jakarta and the disposal of waste derived from economic activities carried out in the coastal areas of North Jakarta. Uncertainty in the search for fish resources makes Cilincing's small scale fishermen have no fixed reguler income and that makes them very vulnerable to fall into poverty. This study used a qualitative approach by doing in-depth interviews and observations in the life of Cilincing’s small scale fishermen. Based on the results of data collection, this study found that the forms of networks utilized by Cilincing’s small scale fishermen is a network between individuals and network between individuals with institutions. They used those networks to obtain informations and access into resources they need to survive.